Determination of polar bear (Ursus maritimus) individual genotype and sex based on DNA extracted from paw-prints in snow - Von Duyke, Andrew L.; Crawford, Justin A.; Quakenbush, Lori; Adams, Jennifer R.; Waits, Lisette P. (Frontiers in Conservation Science, 2023)
Polar bears rely upon sea ice to hunt, travel, and reproduce. Declining sea ice extent and duration has led polar bears to be designated as “threatened” (ESA). Population monitoring is vital to polar bear conservation; but recently, poor sea ice has made traditional aircraft-based methods less viable. These methods largely rely upon the capture and handling of polar bears, and have been criticized over animal welfare concerns. Monitoring polar bears via DNA sampling is a promising option. One common method utilizes biopsy darts delivered from a helicopter to collect DNA, a method that faces similar ice associated challenges to those described above. However, epidermal cells shed from the foot pads of a polar bear into its paw-prints in snow are a source of “environmental DNA” (e-DNA) that can be collected non-invasively on the sea ice or on land for potential use in population monitoring. Mitochondrial DNA (mt-DNA) is used to assess whether polar bear DNA is present within a snow sample, and nuclear DNA (n-DNA) can identify individuals and their sex. The goal of this investigation was to assess the viability of using e-DNA collected from paw-prints in the snow to identify individual polar bears and their sex. Snow was sampled from 13 polar bear trails (10 paw-prints per trail) on the sea ice in the Chukchi and Beaufort seas along the North Slope of Alaska. Species verification was based on a mt-DNA PCR fragment analysis test. Identification of individuals was accomplished by amplifying a multiplex of seven n-DNA microsatellite loci, and sex was determined by the amelogenin gene sex ID marker. Six of the 13 bear trails sampled (46%) yielded consensus genotypes for five unique males and one female. To our knowledge, this is the first time that polar bears have been individually identified by genotype and sex using e-DNA collected from snow. This method is non-invasive, could be integrated into genetic mark-recapture sampling designs, and addresses some of the current challenges arising from poor sea ice conditions. It also can involve, engage, and empower Indigenous communities in the Arctic, which are greatly affected by polar bear management decisions.